A escolha do curso superior no Sistema de Seleção Unificada – SISU : o caso do curso de Enfermagem da Universidade Federal de Mato Grosso, Campus Universitário de Sinop - Flores, Cezar Augusto da Silva (2013)
Higher education is sought for a great part of the Brazilian population, as a strategy for social ascension; however, are not all who manage to enter in this level of education, being the main cause of the insufficient number of slots. Due to this reality, selection mechanisms have been created with the goal of distinguishing the fittest and qualified students to ingress in higher education. In order to address the issue, this research aims to study the process of admission in nursing academic course at the Federal University of Mato Grosso, Campus Sinop, taking as a basis the academic period 2012/1, noting the decision process of the students by the course in the face of this new form of proposal selection by the High School National Exam (Exame Nacional do Ensino Médio) - ENEM/Unified Selection System (Sistema de Seleção Unificada) - SiSU. It is a qualitative research, whose focus is to identify the factors that led students to choose the course of nursing, whereas, in that decision making process, the possible influence of the new ingress forms. Students responded to a questionnaire with open and closed questions of exploratory character that aimed to record, analyze and correlate facts or phenomena concerning the choice of the mode of SiSU system features. It was noted that the choice of the nursing course is related to several factors, such as personal vocation, perception of nursing as a health care profession, family influence and ENEM‟s grade to be compatible with the grade for this course. So, join the new check mechanism, consisting of the ENEM/SiSU, has influenced the choice for entry into nursing course for students who had no initial desire of entering such a course, making that choice as a strategy for higher education. It was concluded that the system ENEM/SiSU represents more of a selection process that is not able to overcome the exclusionary model and it‟s necessary to propose new selection mechanisms aimed at improving the method of choice of the course to confront the contradictions that there are nowadays.